2016
DOI: 10.1002/bbb.1719
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel production using immobilized lipase: feasibility and challenges

Abstract: Fatty acid alkyl esters (FAAE, also known as biodiesel) is one of the best alternatives to fossil fuels. Biodiesel can be synthesized via transesterification of oil with alcohol by either chemical or enzymatic catalysis. In particular, immobilized lipase as biocatalyst for transesterification has recently drawn great attention due to its environmental and economic benefits over conventional chemical catalytic processes. This paper provides an in‐depth review of the feasibility and the challenges of biodiesel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 148 publications
(134 reference statements)
1
65
0
Order By: Relevance
“…Biodiesel is a potential alternative to fossil fuels constituted of monoalkyl fatty acid esters including long chain fatty acids that can be derived from vegetable oil, animal fats, and microbial oil. Furthermore, due to their environmental and economic benefits, lipase-catalyzed biodiesel synthesis is a valid alternative to the conventional chemical catalytic processes [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiesel is a potential alternative to fossil fuels constituted of monoalkyl fatty acid esters including long chain fatty acids that can be derived from vegetable oil, animal fats, and microbial oil. Furthermore, due to their environmental and economic benefits, lipase-catalyzed biodiesel synthesis is a valid alternative to the conventional chemical catalytic processes [6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have also investigated the possibility to exploit Aquasorb as enzyme support for immobilization, with the purpose to improve the enzyme properties [6].…”
Section: Insights In Enzyme Researchmentioning
confidence: 99%
“…Water will affect the structure of the enzyme and excessive water produced during hydrolysis can interfere with methanolysis as a result of the competing hydrolytic reaction [11].…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly because the lipase‐catalyzed processes are less energy intensive and exhibit easy product recovery. Recent studies revealed that lipase‐catalyzed transesterification was found to be effective for biodiesel synthesis using waste oils from food industry, which are cheap, nonedible and abundantly available worldwide . It is interesting to note from another study that lipase‐catalyzed biodiesel production presents advantages over conventional processes in terms of eliminating the problem of saturated monoacylglycerol (MAG), which affects the physical properties of bio‐fuels leading to engine failure.…”
Section: Lipase‐catalyzed Reactionsmentioning
confidence: 99%
“…Recent studies revealed that lipasecatalyzed transesterification was found to be effective for biodiesel synthesis using waste oils from food industry, which are cheap, nonedible and abundantly available worldwide. 3,12,30,34,188,199,207,208 It is interesting to note from another study that lipase-catalyzed biodiesel production presents advantages over conventional processes in terms of eliminating the problem of saturated monoacylglycerol (MAG), which affects the physical properties of bio-fuels leading to engine failure. This issue has been well explored by Padhi et al, 130 and they proposed the conversion of MAG to fatty acid methyl esters (FAMEs) through transesterification of glycerol using the lipase synthesized from Penicillium camemberti.…”
Section: Transesterificationmentioning
confidence: 99%